FACTOR EFFECT SPEECH DELAY ON TODDLER (studies on Graha growing development Jombang) - Indah Sri Wahyunik; . Ruliati; Nita Arisanti (STIKES Insan Cendekia Medika Jombang, 2012)
Many parents worry if his son has yet to smooth talk when seen in terms of the age is past compared with the neighborhood kids, friends, his brothers. This reality in the end often invite of question put to psychologist .The delay in the talk and language should be detected and dealt with from the outset by right methods . Research objectives know the factors that affect delay talk ( speech a delay ) on toddler in graha growing development jombang, The kind of research analytic correlational cross sectional, the population is all toddlers that experienced delays of talk at the clinic graha growing kembang jombang a number of 55 people with the total sample 48 people with tehnik consecutive sampling, the independent variable of factors affect biacara ( delays in communication patterns television parents and environmental ), variable delays talk in toddlers.The collection of data using a questionnaire and sheets observation, data analysis using test whitney mann. The results of research shows that the communication parents with children is mostly lacking as many as 25 people (52,1%) , television show is watched by children almost of half of which is less as many as 23 people (47.9%) , parents relationship, the environment and child almost of half of which is less as many as 23 people (47.9%) , delays in talk that is experienced by the son of the majority of delays in a total of 27 people (56,2 %). The result of analysis test mann whitney obtained р = 0,000 & it; 0.05 which means there is a pattern of communication , television show , the relation of parents and the environment with delays in talk. The conclusion of the results of research that all factors affecting the talk of delay , lack of communication with parents , the election of a television and the relationship is not appropriate and parents can affect the environment not support the talk of delay .